Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/bjs5.23
|View full text |Cite
|
Sign up to set email alerts
|

Trends in breast reconstruction practices in a specialized breast tertiary referral centre

Abstract: BackgroundBreast reconstruction is an important component of multidisciplinary breast cancer management. The practice of breast reconstruction after mastectomy has evolved significantly in the past decade as a result of both increasing mastectomy rates and advances in reconstructive strategy. These changes have significantly influenced the contemporary surgical management of breast cancer. The aim of this study was to examine trends in breast reconstruction after mastectomy in an Irish population.MethodsData w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
1
8
0
1
Order By: Relevance
“…In the inquiry section covering a surgical procedure, breast reconstruction was not included, since this type of procedure was performed at the Department of Plastic and Reconstructive Surgery at the University Medical Centre Maribor and not within our department. Breast reconstruction is an important part of breast cancer management which has evolved significantly in the past decades because of advances in reconstructive strategy 23. It is oncologically safe and associated with high satisfaction rates 24.…”
Section: Discussionmentioning
confidence: 99%
“…In the inquiry section covering a surgical procedure, breast reconstruction was not included, since this type of procedure was performed at the Department of Plastic and Reconstructive Surgery at the University Medical Centre Maribor and not within our department. Breast reconstruction is an important part of breast cancer management which has evolved significantly in the past decades because of advances in reconstructive strategy 23. It is oncologically safe and associated with high satisfaction rates 24.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant radiotherapy (PMRT) may have deleterious effects on breast cosmetic outcomes, quality of life (QOL) and surgical complications after immediate BRR. Previous studies evaluating the impact of PMRT on types of immediate BRR showed its potential feasibility in this setting, with lower morbidity rates compared with those of implant‐based procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies evaluating the impact of PMRT on types of immediate BRR showed its potential feasibility in this setting, with lower morbidity rates compared with those of implant‐based procedures. Surprisingly, the rapid adoption of immediate implant‐based reconstruction in about 70 per cent of women, compared with 34 per cent of autologous procedures when PMRT is recommended, may be influenced by surgeon and patient preferences, regardless of current evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Breast reconstruction improves psychosocial and quality-oflife outcomes for the 40% of breast cancer patients who will require mastectomy to achieve locoregional disease control. 1,2 Rates of mastectomy are currently increasing secondary to increased diagnosis of BRCA and other high-risk genetic mutations and an increased demand for contralateral prophylactic mastectomy. [3][4][5] There is also an increasing trend for patients who are eligible for breast-conserving surgery to opt for mastectomy.…”
Section: Introductionmentioning
confidence: 99%